Comprehensive Review of Financial Management, Resource Allocation, And Quality Assurance in General Healthcare - AlHarkan, Abdullah Hussein Saleh; Alnahdi, Saleh Khamis Hadi; Alsaiari, Amer Eidhah Omar; Al hussain, Hussain Saleh H; Alsaiari, Salem Salmeen Amer; samaida, Hassan awad yaslam; Al Rakhami, Salem Hamad Hezam; Alrajab, Hasan Mohammed; Al sehli, Noora Mohmmed; Alyami, Ali Fahad Hishan (Journal of Ecohumanism, 2024)
Key issues in implementing healthcare delivery, as pointed out above, include financial managerial reports, resources, and quality. This review aims to analyze how these factors interact towards the realization of the best patient take while at the same time observing cost control. Financial management is a set of practices that helps maintain efficient expenditure and incomes; resource management is also directed towards the proper utilization of human and other materials, whereas quality management assures right, standard, and patient-centered services. This report is built using the aggregation of the latest research and some data from multiple healthcare systems worldwide, arguments, together with novel presented evidence, figures, and tactical solutions. This way, it identifies issues like gaps in funding and shortages of resources in the healthcare workforce and frames an integrated direction for improving healthcare delivery.